Vps54 Regulates Lifespan and Locomotor Behavior in Adult Drosophila melanogaster - Wilkinson, Emily C.; Starke, Emily L.; Barbee, Scott A. (Frontiers in Genetics, 2021)
Vps54 is an integral subunit of the Golgi-associated retrograde protein (GARP) complex, which is involved in tethering endosome-derived vesicles to the trans-Golgi network (TGN). A destabilizing missense mutation in Vps54 causes the age-progressive motor neuron (MN) degeneration, muscle weakness, and muscle atrophy observed in the wobbler mouse, an established animal model for human MN disease. It is currently unclear how the disruption of Vps54, and thereby the GARP complex, leads to MN and muscle phenotypes. To develop a new tool to address this question, we have created an analogous model in Drosophila by generating novel loss-of-function alleles of the fly Vps54 ortholog (scattered/scat). We find that null scat mutant adults are viable but have a significantly shortened lifespan. Like phenotypes observed in the wobbler mouse, we show that scat mutant adults are male sterile and have significantly reduced body size and muscle area. Moreover, we demonstrate that scat mutant adults have significant age-progressive defects in locomotor function. Interestingly, we see sexually dimorphic effects, with scat mutant adult females exhibiting significantly stronger phenotypes. Finally, we show that scat interacts genetically with rab11 in MNs to control age-progressive muscle atrophy in adults. Together, these data suggest that scat mutant flies share mutant phenotypes with the wobbler mouse and may serve as a new genetic model system to study the cellular and molecular mechanisms underlying MN disease.